Improving women's team performance on corners through video training and ball trajectory anticipation - Libreau, Clement; Benguigui, Nicolas (Frontiers in Psychology, 2025)
The aim of this study was to assess the effectiveness of a video-based perceptual training programme designed to enhance anticipation skills in professional female football players. The video reference task was used to test participants in pre- and post-tests, where they predicted the ball's arrival location during corners. Participants were evenly divided into an experimental group, which received training in the task between the pre- and post-tests using a progressive temporal occlusion method, and a control group, which received no training. The rate of correct responses, response time, and confidence scores were analyzed in the reference task, as well as performance on corners in real matches, to assess the expected transfer of learning to the field. The results revealed that the experimental group, which underwent training, significantly improved their precision in predicting the ball's landing zone after the intervention, with their accuracy score increasing from 54% to 68% (p < 0.05, η2 = 0.60). Additionally, their response time decreased from 3.2 to 2.4 s (p < 0.05, η2 = 0.48), and their confidence score improved from 3 to 3.8 (p < 0.05, η2 = 0.76). This effect slightly diminished after a 6-month retention interval but remained significantly higher than at the pre-test. Furthermore, we observed that the performance of professional football players during corners in actual matches improved, suggesting a positive effect of the video-based perceptual-cognitive training.